Digital Business Models In The Development Of Modern Agriculture: An Empirical Study In Farmer Communities - Zidnal Falah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research aims to analyze the application of digital business models in the development of modern agriculture, with a focus on the farming community in Cirebon Regency. The background of the research is based on the fact that the agricultural sector in Indonesia still faces various challenges such as low productivity, limited market access, and dependence on traditional distribution chains. Digital transformation is believed to be able to be a strategic solution to increase efficiency, expand market access, and strengthen the competitiveness of smallholders. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with farmer group leaders and digital assistants, distribution of questionnaires to farmers who have participated in digitalization training, and field observations during one planting cycle. The results of the study show that the digital business model provides real benefits in the form of increased online market access, production recording efficiency, and local innovation opportunities. However, significant barriers remain, especially the limitations of digital literacy, internet infrastructure, and social resistance. Community-based adaptation strategies, such as the role of millennial farmers as digital agents and peer learning systems, have proven effective in supporting the transformation process. This study concludes that digital business models have great potential in strengthening the sustainability of modern agriculture, noting that there is more comprehensive ecosystem support.